An annotated checklist of earwigs (Dermaptera) of South India with two new records from India - Karthik, C. M.; Kalleshwaraswamy, C. M. (Zootaxa, 2023)
The checklist of earwigs occurring in South India, viz., Andhra Pradesh, Karnataka, Kerala, Tamil Nadu and Telangana, was compiled from published literature and augmented by collecting efforts between 2020 and 2022. A total of 102 species belonging to 45 genera and eight families are listed herein from South India. Specimens representing 29 species were collected from the South Indian states during 2020–2022 surveys, of which Dendroiketes corticinus and Chaetospania anderssoni represent two new records for India. The highest number of species was recorded from Tamil Nadu (79 species), followed by Karnataka (39 species) and Kerala (26 species), while the least number were from Telangana (6) and Andhra Pradesh (4 species). The records indicated that the South Indian states, which cover a significant portion of the Western Ghats of India (Karnataka, Kerala and Tamil Nadu), are more diverse than previously indicated.